Algae-shaped zirconium-copper-nickel-iron-cobalt eutectic high-entropy alloy and preparation method thereof
The preparation of seaweed-like zirconium copper nickel iron-cobalt-based eutectic high-entropy alloys through vacuum arc smelting method has solved the problem of many casting defects in traditional high-entropy alloys, and achieved high-strength and high-plastic eutectic high-entropy alloys, which are suitable for aerospace, chemical and other fields.
Patent Information
- Application Number
- CN202510572469.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-05-06
- Publication Date
- 2025-07-18
AI Technical Summary
The existing high-entropy alloys lack phase diagram reference when designing components, making it difficult to prepare a complete eutectic structure, resulting in many casting defects and poor fluidity, which limits its large-scale application in aerospace, chemical and other fields.
A seaweed-like zirconium copper nickel iron-cobalt-based eutectic high-entropy alloy was prepared by vacuum arc smelting. By controlling the melting point of the raw material and deoxygenation treatment, a uniform seaweed-like eutectic structure was formed, including the specific atomic percentage composition of Zr, Cu, Ni, Fe, and Co., and the ingot was melted and flipped several times to ensure purity and tissue uniformity.
The combination of high strength and high plasticity is achieved, the compressive strength reaches 1187.9MPa, the hardness is 283.4HV, and the plastic strain can reach 26.29%, which significantly improves the casting performance and mechanical properties of the alloy, reduces casting defects, and is suitable for high-temperature and high-load environments.
Smart Images

Figure CN120330573A_ABST
Abstract
Description
Technical Field
[0001] The present invention provides a seaweed-like zirconium copper nickel iron cobalt-based eutectic high-entropy alloy and a preparation method thereof, belonging to the technical field of high-entropy alloys. Background Art
[0002] High-entropy alloy materials are mainly new alloy materials with a multi-principal element uniformly distributed and high structural stability, which are made by uniformly mixing five or more elements. Due to the fact that high-entropy alloys can maintain their structural stability and good performance in harsh environments such as high temperature and high pressure, in recent years, high-entropy alloys have been widely used in the fields of aerospace, chemical engineering, energy, etc.
[0003] Traditional high-entropy alloys are mostly single solid-solution phases, generally having a BCC, FCC or HCP structure. At present, most high-entropy alloys are prepared by melting and casting. The poor casting fluidity and obvious casting defects of the high-entropy alloys with a single solid-solution structure limit the large-scale industrial application of high-entropy alloys. Considering that eutectic alloys undergo isothermal transformation and there is no specific solidification interval, eutectic alloys have good fluidity, which is beneficial to reducing defects and segregation during the casting process. Combining the advantages of eutectic alloys and high-entropy alloys to form a new alloy system, eutectic high-entropy alloys combine the advantages of traditional eutectic alloys with uniform composition and good castability and high-entropy alloys with high phase stability and excellent mechanical properties. It is a self-generated two-phase composite material with a lamellar heterogeneous structure composed of a two-phase composition. As an important branch in the research field of high-entropy alloys, it exhibits excellent comprehensive performance by virtue of its unique eutectic microstructure characteristics. Eutectic high-entropy alloys form a stable eutectic microstructure by reasonably designing a multi-element alloy system, which is usually composed of alternating soft and hard phases, effectively coordinating the contradiction between strength and plasticity and overcoming the strong-plasticity inversion problem commonly existing in traditional high-entropy alloys. In addition, the formation of the eutectic microstructure significantly reduces the solidification temperature of the alloy, improving its castability and processing performance. Based on its excellent mechanical properties, good wear resistance, corrosion resistance and high thermal stability, eutectic high-entropy alloys have broad application prospects in the fields of aerospace, high-end equipment manufacturing, energy chemical engineering, nuclear industry and ocean engineering, and are especially suitable for key structural materials that withstand high temperature, high load and harsh service environments. However, high-entropy alloys are composed of five to six elements, and there is no ready-made phase diagram for reference in the composition design. There are certain challenges in designing and preparing eutectic high-entropy alloys with a complete eutectic microstructure.
[0004] At present, the research on eutectic high-entropy alloys is still in its infancy, and more excellent eutectic high-entropy alloys still need to be further developed and studied. Summary of the Invention
[0005] Based on this, the present invention provides a seaweed-like zirconium-copper-nickel-iron-cobalt-based eutectic high-entropy alloy and a preparation method thereof. The zirconium-copper-nickel-iron-cobalt-based high-entropy alloy of the present invention has a seaweed-like eutectic structure, with a compressive strength of 1187.9 MPa, a hardness of 283.4 HV, and a plastic strain that can reach 26.29%. This eutectic high-entropy alloy has very excellent alloy fluidity and casting performance, is not prone to forming casting defects, and has excellent comprehensive mechanical properties. Potential application scenarios include the casting and forming of large propellers, etc.
[0006] For the seaweed-like zirconium-copper-nickel-iron-cobalt-based eutectic high-entropy alloy of the present invention, its chemical composition is as follows:
[0007] Zr a Cu b Ni c Fe d Co e ,
[0008] where a, b, c, d, and e are the atomic percentages of the corresponding elements respectively, 8.1% ≤ a ≤ 12.5%, 20.5% ≤ b ≤ 28.0%, 19.0% ≤ c ≤ 26.7%, 17.0% ≤ d ≤ 24.5%, 19.0% ≤ d ≤ 26.0%, and a + b + c + d + e = 100%.
[0009] It can be seen from the crystal phase structure diagram of the zirconium-copper-nickel-iron-cobalt-based eutectic high-entropy alloy of the present invention that it has a uniform seaweed-like eutectic structure.
[0010] The present invention also provides a preparation method for the seaweed-like zirconium-copper-nickel-iron-cobalt-based eutectic high-entropy alloy, which includes the following steps:
[0011] (1) Weigh the raw materials Zr, Cu, Ni, Fe, and Co according to the chemical composition of the high-entropy alloy, and put the weighed raw materials into the crucible of the vacuum arc melting furnace in order of increasing melting point;
[0012] (2) Perform deoxidation treatment on the vacuum arc melting furnace;
[0013] (3) After the deoxidation treatment, continue to heat up to melt the raw materials in step (1), and obtain an alloy ingot after cooling; after repeatedly melting the alloy ingot, a zirconium-copper-nickel-iron-cobalt-based eutectic high-entropy alloy is obtained.
[0014] Preferably, before weighing the raw materials in step (1), it is necessary to remove the oxide scale on the surface of the raw materials and ultrasonically clean them to ensure that the purity of the raw materials ≥ 99.9 wt.%.
[0015] Preferably, in step (1), the raw material with the lowest melting point is placed at the bottom layer of the crucible, and the raw material with the highest melting point is placed at the upper layer of the crucible.
[0016] Preferably, the deoxygenation treatment in step (2) is to place a crucible containing a titanium ingot in the vacuum arc melting furnace and vacuum melt the titanium ingot to absorb oxygen.
[0017] More preferably, the deoxygenation treatment in step (2) is to first evacuate to 5×10 -3 Pa, then fill it with inert atmosphere to 0.05-0.06MPa, and then heat up to melt the titanium ingot.
[0018] Preferably, the current for melting the raw materials in step (3) is 200-300A, and the arc is maintained for 3-4 minutes after melting.
[0019] Preferably, the smelting is repeated for more than 5 times in step (3), and the ingot needs to be turned over after each smelting.
[0020] Compared with the prior art, the present invention has the following beneficial effects:
[0021] The present invention provides a seaweed-like zirconium-copper-nickel-iron-cobalt eutectic high entropy alloy and a preparation method thereof. The metallographic structure of the high entropy alloy prepared by the method presents a seaweed-like structure, and the alloy is a eutectic high entropy alloy. After testing, the zirconium-copper-nickel-iron-cobalt eutectic high entropy alloy of the present invention is composed of CuFeNi phase and Fe 11 The Co5 phase is composed of two phases, with a compressive strength of 1187.9MPa, a hardness of 283.4HV, and a plastic strain of 26.29%. It has very excellent alloy fluidity and casting properties. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1 The Zr provided in Example 1 of the present invention 9.4 Cu 22.9 Ni 22.8 Fe 22.4 Co 22.5 Metallographic microstructure of high entropy alloy;
[0023] Figure 2 The Zr provided in Example 1 of the present invention 9.4 Cu 22.9 Ni 22.8 Fe 22.4 Co 22.5 Metallographic microstructure of high entropy alloy;
[0024] Figure 3 The Zr provided in Example 1 of the present invention 9.4 Cu 22.9 Ni 22.8 Fe 22.4 Co 22.5 Backscattered SEM image of high entropy alloy;
[0025] Figure 4The Zr provided in Embodiment 1 of the present invention 9.4 Cu 22.9 Ni 22.8 Fe 22.4 Co 22.5 Micro-area XRD pattern of the high-entropy alloy;
[0026] Figure 5 The Zr provided in Embodiment 1 of the present invention 9.4 Cu 22.9 Ni 22.8 Fe 22.4 Co 22.5 Room-temperature compression stress-strain curve of the high-entropy alloy;
[0027] Figure 6 The Zr provided in Embodiment 2 of the present invention 11.8 Cu 25.6 Ni 23.1 Fe 19.5 Co 20 Metallographic microstructure diagram of the high-entropy alloy;
[0028] Figure 7 The Zr provided in Embodiment 2 of the present invention 11.8 Cu 25.6 Ni 23.1 Fe 19.5 Co 20 Backscattered SEM image of the high-entropy alloy;
[0029] Figure 8 The Zr provided in Embodiment 2 of the present invention 11.8 Cu 25.6 Ni 23.1 Fe 19.5 Co 20 Room-temperature compression stress-strain curve of the high-entropy alloy. Detailed implementation manners
[0030] To make the objectives, technical solutions, and advantages of the present invention clearer, the preferred implementation manners of the present invention will be further described in detail below with reference to the embodiments. All other embodiments obtained by those of ordinary skill in the art based on the embodiments of the present invention without creative efforts shall fall within the scope of protection of the present invention.
[0031] Embodiment 1
[0032] A preparation method of a Zr 9.4 Cu 22.9 Ni 22.8 Fe 22.4 Co 22.5 high-entropy alloy is as follows:
[0033] (1) Clean Zr, Cu, Ni, Fe, and Co first to remove the scale on the surface of the raw materials and ultrasonically clean them to ensure that the purity of the raw materials is ≥ 99.9 wt.%;
[0034] Then, according to the chemical composition of the Zr 9.4 Cu 22.9 Ni 22.8 Fe 22.4 Co 22.5 high-entropy alloy, weigh the cleaned Zr, Cu, Ni, Fe, and Co, and put the weighed raw materials into the crucible of the vacuum arc melting furnace in order of melting point from low to high. Specifically, put the raw material with the lowest melting point at the bottom layer of the crucible and the raw material with the highest melting point at the upper layer of the crucible;
[0035] (2) Place a crucible containing titanium ingots in the vacuum arc melting furnace. First, evacuate to 5×10 -3 Pa, then fill it with an inert atmosphere to 0.06 MPa, and then heat up to melt the titanium ingot for oxygen absorption;
[0036] (3) After the deoxidation treatment, continue to heat up to melt the raw materials in step (1). The current for melting the raw materials is 250 A. After melting, keep the arc for 3 minutes, and then cool to obtain an alloy ingot; Repeat the melting of the alloy ingot 6 times, and it is necessary to turn the ingot over after each melting. Finally, obtain the Zr 11.8 Cu 25.6 Ni 23.1 Fe 19.5 Co 20 high-entropy alloy.
[0037] Example 2
[0038] A method for preparing a Zr 11.8 Cu 25.6 Ni 23.1 Fe 19.5 Co 20 high-entropy alloy is as follows:
[0039] (1) Clean Zr, Cu, Ni, Fe, and Co first to remove the scale on the surface of the raw materials and ultrasonically clean them to ensure that the purity of the raw materials is ≥ 99.9 wt.%;
[0040] Then, according to the chemical composition of the Zr 11.8 Cu 25.6 Ni 23.1 Fe 19.5 Co 20 high-entropy alloy, weigh the cleaned Zr, Cu, Ni, Fe, and Co, and put the weighed raw materials into the crucible of the vacuum arc melting furnace in order of melting point from low to high. Specifically, put the raw material with the lowest melting point at the bottom layer of the crucible and the raw material with the highest melting point at the upper layer of the crucible;
[0041] (2) Place a crucible containing titanium ingots in the vacuum arc melting furnace, first evacuate to 5×10 -3 Pa, then fill with an inert atmosphere to 0.06 MPa, and then raise the temperature to melt the titanium ingots for oxygen absorption;
[0042] (3) After the deoxidation treatment, continue to raise the temperature to melt the raw materials described in step (1), where the current for melting the raw materials is 250 A, keep the arc for 3 minutes after melting, and obtain an alloy ingot after cooling; repeatedly melt the alloy ingot 6 times, and it is necessary to turn the ingot after each melting, and finally obtain Zr 11.8 Cu 25.6 Ni 23.1 Fe 19.5 Co 20 high-entropy alloy.
[0043] Effect test
[0044] Perform metallographic microscope and backscattered SEM image detection on the Zr 9.4 Cu 22.9 Ni 22.8 Fe 22.4 Co 22.5 high-entropy alloy prepared in Example 1. The test results are as Figures 1 - 3 shown. The results show that the microstructure of the Zr 9.4 Cu 22.9 Ni 22.8 Fe 22.4 Co 22.5 high-entropy alloy prepared by the present invention is composed of seaweed-like eutectic structure.
[0045] Perform XRD pattern detection on the Zr 9.4 Cu 22.9 Ni 22.8 Fe 22.4 Co 22.5 high-entropy alloy prepared in Example 1. The results are as Figure 4 shown. The structure of the Zr 9.4 Cu 22.9 Ni 22.8 Fe 22.4 Co 22.5 high-entropy alloy prepared by the present invention consists of two phases, namely the CuFeNi phase with a face-centered cubic structure and the Fe 11 Co5 phase with a tetragonal structure;
[0046] Perform on the Zr 9.4 Cu 22.9 Ni 22.8 Fe 22.4 Co 22.5The Zr-based high-entropy alloy was subjected to room-temperature compression engineering stress testing, and the test results are as Figure 5 shown. The Zr 9.4 Cu 22.9 Ni 22.8 Fe 22.4 Co 22.5 high-entropy alloy prepared in the present invention has a yield strength of 386.1 MPa, a compressive strength of 1187.9 MPa, and a plastic strain of 26.29% at room temperature.
[0047] The Zr 9.4 Cu 22.9 Ni 22.8 Fe 22.4 Co 22.5 high-entropy alloy prepared in Example 1 was subjected to Vickers hardness testing. There were 15 test points, which were evenly distributed on the surface of the alloy. The results are shown in Table 1:
[0048] Table 1 Vickers hardness test results of the Zr 9.4 Cu 22.9 Ni 22.8 Fe 22.4 Co 22.5 high-entropy alloy
[0049] Hardness test points <![CDATA[Vickers hardness value (HV 0.1 )]]> 1 287.91 2 234.53 3 274.85 4 282.58 5 285.23 6 301.92 7 299.04 8 269.88 9 282.58 10 299.04 11 282.58 12 274.85 13 287.91 14 320.12 15 267.44 Average value 283.36
[0050] As can be seen from Table 1, the Vickers hardness value of the Zr 9.4 Cu 22.9 Ni 22.8 Fe 22.4 Co 22.5 high-entropy alloy prepared in the present invention is 283.36 HV.
[0051] The Zr 11.8 Cu 25.6 Ni 23.1 Fe 19.5 Co 20 high-entropy alloy prepared in Example 2 was subjected to metallographic microscope and backscattered SEM image testing. The test results are as Figure 7 shown. The results show that the microstructure of the Zr 11.8 Cu 25.6 Ni 23.1 Fe 19.5 Co 20 high-entropy alloy prepared in the present invention is composed of seaweed-like eutectic structure.
[0052] The Zr 11.8 Cu 25.6 Ni 23.1 Fe 19.5 Co 20The high-entropy alloy was subjected to room-temperature compression engineering stress testing, and the test results are as follows Figure 8 shown. The Zr 11.8 Cu 25.6 Ni 23.1 Fe 19.5 Co 20 high-entropy alloy prepared in the present invention has a room-temperature yield strength of 359.7 MPa, a compressive strength of 939.7 MPa, and a plastic strain of 31.28%.
[0053] For the Zr 11.8 Cu 25.6 Ni 23.1 Fe 19.5 Co 20 high-entropy alloy prepared in Example 2, Vickers hardness testing was carried out. The number of test points was 15, which were evenly distributed on the alloy surface. The results are shown in Table 2:
[0054] Table 2 Vickers hardness test results of Zr 11.8 Cu 25.6 Ni 23.1 Fe 19.5 Co 20 high-entropy alloy
[0055] Hardness test points <![CDATA[Vickers hardness value (HV 0.1 )]]> 1 287.91 2 316.97 3 262.67 4 253.49 5 290.63 6 269.88 7 272.35 8 296.19 9 299.04 10 304.84 11 313.87 12 277.39 13 265.04 14 293.39 15 240.60 Average value 282.95
[0056] As can be seen from Table 2, the Vickers hardness value of the Zr 11.8 Cu 25.6 Ni 23.1 Fe 19.5 Co 20 high-entropy alloy prepared in the present invention is 282.9 HV.
[0057] The embodiments described above are some, but not all, of the embodiments of the present invention. The detailed description of the embodiments of the present invention is not intended to limit the scope of the claimed invention, but merely represents selected embodiments of the present invention. All other embodiments obtained by those of ordinary skill in the art based on the embodiments of the present invention without creative efforts fall within the scope of protection of the present invention.
Claims
1. A seaweed-like zirconium copper nickel iron cobalt-based eutectic high-entropy alloy, characterized in that, The chemical composition of the eutectic high-entropy alloy is as follows: Zr a Cu b Ni c Fe d Co e , Where a, b, c, d, and e are the atomic percentages of the corresponding elements, 8.1% ≤ a ≤ 12.5%, 20.5% ≤ b ≤ 28.0%, 19.0% ≤ c ≤ 26.7%, 17.0% ≤ d ≤ 24.5%, 19.0% ≤ d ≤ 26.0%, and a + b + c + d + e = 100%.
2. The zirconium-copper-nickel-iron-cobalt-based eutectic high-entropy alloy according to claim 1, wherein The eutectic high-entropy alloy has a seaweed-like eutectic microstructure, consisting of a CuFeNi phase and an Fe 11 Co5 phase, which are two phases.
3. The preparation method of the seaweed-like zirconium copper nickel iron cobalt-based eutectic high-entropy alloy according to claim 1 or 2, characterized in that, It includes the following steps: (1) Weigh the raw materials Zr, Cu, Ni, Fe, and Co according to the chemical composition of the high-entropy alloy, and place the weighed raw materials into the crucible of the vacuum arc melting furnace in order of melting point from low to high; (2) Perform deoxidation treatment on the vacuum arc melting furnace; (3) After the deoxidation treatment, continue to heat up to melt the raw materials described in step (1), and obtain an alloy ingot after cooling; after repeatedly melting the alloy ingot, a zirconium-copper-nickel-iron-cobalt-based eutectic high-entropy alloy is obtained.
4. The preparation method of the algal zirconium copper nickel iron cobalt-based eutectic high-entropy alloy according to claim 3, characterized in that, Before weighing the raw materials in step (1), the oxide scale on the surface of the raw materials needs to be removed and ultrasonically cleaned to ensure that the purity of the raw materials ≥ 99.9 wt.%.
5. The preparation method of the algal zirconium copper nickel iron cobalt-based eutectic high-entropy alloy according to claim 3, characterized in that, In step (1), the raw material with the lowest melting point is placed at the bottom layer of the crucible, and the raw material with the highest melting point is placed at the upper layer of the crucible.
6. The preparation method of the algal zirconium copper nickel iron cobalt-based eutectic high-entropy alloy according to claim 3, characterized in that The deoxidation treatment in step (2) is to place a crucible containing titanium ingots in the vacuum arc melting furnace and vacuum-melt the titanium ingots to absorb oxygen.
7. The preparation method of the algal zirconium copper nickel iron cobalt-based eutectic high-entropy alloy according to claim 6, characterized in that The deoxidation treatment described in step (2) is to first evacuate to 5×10 -3 Pa, then fill with an inert atmosphere to 0.05 - 0.06 MPa, and then heat up to melt the titanium ingot.
8. The preparation method of the algal zirconium copper nickel iron cobalt-based eutectic high-entropy alloy according to claim 3, characterized in that, In step (3), the current for melting the raw materials is 200 - 300 A, and the arc is maintained for 3 - 4 minutes after melting.
9. The preparation method of the algal zirconium copper nickel iron cobalt-based eutectic high-entropy alloy according to claim 3, wherein The number of times of repeated melting in step (3) is more than 5 times, and the ingot needs to be flipped after each melting.